Bacteremia After Orthodontic Separators Placement in Orthodontic Patients: A Randomized Clinical Trial - Al-Qamesh, Najla Abdullrazzaq Ayedh Shalan (University of Science and Technology, Sana'a, 2024)
The purpose of this study was to detect the occurrence of bacteremia following the placement of orthodontic separators in 2 groups of patients treated with orthodontic fixed appliances with and without the use of mouthwash. A total of 40 patients (12 males and 28 females with age from (17-35 years) receiving orthodontic treatment were selected from dental clinic at the University of Science and Technology Hospital, Sana’a, Yemen. For both groups, pre- and post-operative venous blood samples were obtained from the participants by the aseptic technique. Aspiration was done immediately before (control sample) and 5 minutes from placement of the orthodontic separators (study sample). Participants in group A were started with aspiration the pre-operative blood sample then the orthodontic separators were placed then after 2-5mins the post-operative blood sample were aspirated. Participants in group B were requested to rinse with chlorhexidine mouth wash before the pre-operative blood sample aspiration The blood samples were monitored with an automated detection system for aerobic and anaerobic samples. The detection continued for 8 days. The study results revealed that all blood samples recorded negative bacteremia at baseline (except one was excluded) and following placement of separator. The laboratory findings of the tested blood samples were all negative for bacteremia. The study concluded that it may be stated that orthodontic separator placement is not a causative factor of bacteremia.
Keywords: Bacteremia; Orthodontic separators; Randomized clinical trial; Orthodontic patients